The role of social media eWOM and motivation typology in urban Islamic digital donations - Anggara, Muhamad Rafi; Jono Mintarto Munandar; Irfan Syauqi Beik (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study examines how the credibility and usefulness of social media electronic word of mouth (eWOM) affects information adoption and how it subsequently influences donor engagement, donation intention, and donation decisions among urban Muslims in Indonesia. It also explores differences in donation behavior based on the motivation type.Methodology – This study employed a quantitative approach using survey data from 230 Muslim respondents in Greater Jakarta. The analysis utilized descriptive statistics and Structural Equation Modeling with Partial Least Squares (SEM-PLS), including outer model evaluation (validity and reliability) and inner model analysis (hypothesis testing).Findings – All proposed hypotheses are supported. eWOM credibility is the strongest predictor of information adoption, significantly enhancing donor engagement, donation intention, and actual donation decisions. Donor engagement further increases intention, which strongly predicts decisions. The descriptive results show that humanitarian donations are the most dominant, particularly among young Muslim women aged 20–24, driven by empathy and social media engagement. Instagram is the primary reference source and Kitabisa.com is the most frequently used donation platform.Implications – This research is useful for digital fundraising platforms and NGOs that aim to improve engagement by focusing on emotionally credible content, platform usability, and micro-donation options, especially for humanitarian and crowdfunding campaigns targeting younger Muslim donors.Originality – This study contributes to the literature by integrating descriptive donation motivation typologies with SEM-PLS analysis to provide a comprehensive understanding of digital Islamic philanthropic behavior among urban Muslim communities.